Investigating Denominational and Church Attendance Differences in Obesity and Diabetes in Black Christian Men and Women - Bentley-Edwards, Keisha L.; Blackman Carr, Loneke T.; Conde, Eugenia; Darity, William A. Jr. 1953-; Robbins, Paul. A.; Zaw, Khaing (2020)
Prior investigations of the relationships between religious denomination and diabetes and obesity do not consider the nuance within black faith traditions. This study used data from the National Survey of American Life (n = 4344) to identify denominational and religious attendance differences in obesity and diabetes among black Christian men and women. Key findings indicated that black Catholics and Presbyterians had lower odds of diabetes than Baptists. Black men that attended church almost daily were nearly twice as likely to be obese than those that never attend services. These results indicate that denomination and gender should inform faith-based and placed health promotion approaches.
Keywords: African Americans; Denomination; Diabetes; Obesity; Religion